Sertifikasi Halal pada Produk UMKM di Aceh : Tinjauan atas Implementasi Qanun Nomor 8 Tahun 2016 tentang Sistem Jaminan Produk Halal - Fauzan, Muhammad; Maulana, Muhammad (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2025)
This study is to evaluate the efficacy of the implementation of Aceh Qanun Number 8 of 2016 about the Halal Product Guarantee System in enhancing the quality of products and packaging for Micro, Small, and Medium Enterprises (MSMEs) in Aceh. The study employs a descriptive qualitative methodology, utilizing literature reviews derived from legal statutes, statistics from the Statistics Indonesia (BPS), reports from the Aceh Cooperatives and SMEs Office, and various pertinent scientific publications. The study's findings indicate that the Aceh Ulama Consultative Assembly (MPU) and LPPOM's implementation of halal certification is still facing a number of challenges. These include high certification costs, a lack of knowledge about halal among MSME actors, and ineffective supervision and mentoring systems at the district and city levels. However, halal certification has been shown to help improve the quality of products and packaging, promote cleaner and more sanitary production methods, and boost consumer trust in local goods. Halal certification is not only a way to enforce rules, but it also plays a strategic role in making the economy more competitive in the region and helping the concepts of maqāṣid al-syarī'ah to be used in the business world. This study is limited as it is conceptual and literature-based; thus, more research employing an empirical approach is advised to achieve a more full understanding of the impact of halal certification in Aceh.